Stability and Chaos in Celestial Mechanics - Celletti, Alessandra; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book presents classical celestial mechanics and its interplay with dynamical systems in a way suitable for advance level undergraduate students as well as postgraduate students and researchers. First paradigmatic models are used to introduce the reader to the concepts of order, chaos, invariant curves, cantori. Next the main numerical methods to investigate a dynamical system are presented. Then the author reviews the classical two-body problem and proceeds to explore the three-body model in order to investigate orbital resonances and Lagrange solutions. In rotational dynamics the author details the derivation of the rigid body motion, and continues by discussing related topics, from spin-orbit resonances to dumbbell satellite dynamics. Perturbation theory is then explored in full detail including practical examples of its application to finding periodic orbits, computation of the libration in longitude of the Moon. The main ideas of KAM theory are provided including a presentation of long-term stability and converse KAM results. Celletti then explains the implementation of computer-assisted techniques, which allow the user to obtain rigorous results in good agreement with the astronomical expectations. Finally the study of collisions in the solar system is approached.
Order and chaos -- Numerical dynamical methods -- Kepler$1 (Bs problem -- The three-body problem and the Lagrangian solutions -- Rotational dynamics -- Perturbation theory -- Invariant tori -- Long-time stability -- Determination of periodic orbits -- Regularization theory.s
Keywords: Physics; Mathematical physics; Mechanics; Astrophysics; Physics; Extraterrestrial Physics, Space Sciences; Astrophysics and Astroparticles; Mechanics; Statistical Physics, Dynamical Systems and Complexity; Mathematical Methods in Physics